Acculturation and the labor market in Mexico - Javier Cano-Urbina; Patrick L. Mason (IZA Journal of Labor Policy, 2016)
This paper empirically examines the relationship between the self-identity as Indigenous and earnings inequality in the Mexican labor market. Using Mexican Census data and a large set of wage covariates reveals the existence of an earnings penalty for self-identification as Indigenous. There is an additional and larger penalty for Indigenous persons who are fluent in an Indigenous language, regardless of Spanish language fluency. Further analyses using the Mexican Family Life Survey reveal that these earnings gaps persist after we also control for an individual's cognitive ability. Ethno-linguistic inequality is particularly strong in smaller cities and among self-employed workers.
Keywords: J10; J15; J31; J71; O15; 330; Developing country; Indigenous peoples; Demographic economics; Wage gap; Discrimination; Minorities